Microwave Irradiation Assisted Supercritical Carbon Dioxide Extraction of Bio-Oils from Chlorella Vulgaris Microalgae - N. Ibrahim, S.; A. Radzun, K.; Ismail, K. (International Journal of Engineering and Technology, 2019)
Chlorella vulgaris is one of the promising microalgae strains that can produce high yield of bio-oils. The C. vulgaris was pretreated with microwave irradiation prior to extraction using supercritical carbon dioxide (SCCO2). Fourier transform infrared spectroscopy (FTIR) analysis showed microwave irradiation pretreatment does not affect the material composition of C. vulgaris. Scanning electron microscopy (SEM) of the microwave irradiation pretreated microalgae showed an agglomeration of the cells with the cells shape became distorted due to rupturing of the cell walls. Optimization of the SCCO2 process parameters (pressure, temperature and CO2 flow rate) was performed by using response surface methodology (RSM) with central composite design (CCD). Two factors significantly affecting the extraction yield were temperature and pressure. The model equation also predicted the optimum condition for the SCCO2 (without microwave pretreatment) at 70 , 5676 psi and 7 sL/ min while optimum condition for SCCO2 (microwave irradiation pretreatment) at 63 , 5948 psi and 10 sL/ min. High amount of saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), -linolenic acid and palmitoleic acid were found in the extracted oil with microwave irradiation pre-treatment sample.Â  In addition, the polyunsaturated fatty acids (PUFA) content in the microwave irradiation pretreated oil was considerably low and is desirable for biodiesel production.Â